Human Rights Based Law Protection Model for the Mental, Spiritual and the Healing Victims of Child Trafficking In Indonesia - 1 Sulistya Eviningrum, 2 Hartiwiningsih Hartiwiningsih, 3 Mohamad Jamin (Indian Journal of Forensic Medicine & Toxicology, 2020)
Abstract: The protection needed by children to face the reality of being the victims of child trafficking is not only physical protection, but mental, spiritual, and social healing as well. The punishment system still focuses on criminals instead of the victims. The law protection model for the victims of child trafficking in Indonesia is not comprehensive, so there is little chance that the victims get their rights. Although Act Number 21 Year 2007 has guaranteed the victims’ rights, the chance to get their rights is relatively minimal.